Antibiotic Sensitivity Test on Staphylococcus Aureus Detected in Sputum of Patients with Pneumonia Treated in Hospitals - Dini Agustina; Diana Chusna Mufida; Hanifa Rizki A.S.; Dion Krismashogi Dharmawan (Faculty of Medicine, University of Jember, 2019)
Pneumonia is a respiratory tract infection that attacks the pulmonary parenchyma. This disease can be caused by bacteria, one of which is Staphylococcus aureus. Antibiotics have an important role to play in reducing the morbidity and mortality incidence of pneumonia, but currently, the incidence of resistance antibiotics is increased. The purpose of this study was to determine the sensitivity of antibiotics Staphylococcus aureus in pneumatic sputum patients. The design of this study was observational descriptive, using sputum samples from pneumonia patients in Subandi and Paru Jember hospitals in November to December 2018. The identification of bacteria in sputum was continued by testing the sensitivity of bacteria to antibiotics. The antibiotics used in this study were chloramphenicol, gentamicin, amikacin, levofloxacin, ampicillin-sulbactam, cotrimoxazole, and ciprofloxacin — data obtained in the frequency distribution table. Of the ten sputum that was successfully cultured, four Gram-negative bacilli bacteria and six Gram-positive coccus bacteria were obtained. The results approved the six Gram-positive coccus bacteria, detected as Staphylococcus aureus. The antibiotic resistance of Staphylococcus aureus to ampicillin-sulbactam was high. Keywords: antibiotic sensitivity, bacteria, pneumonia